Glutamatergic metabolite correlations with neuropsychological tests in first episode schizophrenia. Issue 2 (30th August 2015) - Dempster, Kara; Norman, Ross; Théberge, Jean; Densmore, Maria; Schaefer, Betsy; Williamson, Peter
Abstract: Increased glutamatergic metabolites have been found in first episode schizophrenia. Although abnormal neuropsychological functioning has been demonstrated to be a core feature of schizophrenia, no studies have examined glutamatergic metabolites and neuropsychological function in drug-naïve patients. The present study addressed whether higher levels of glutamatergic metabolites would be associated with poorer neuropsychological performance and social functioning in first episode patients. Glutamatergic concentration estimates were obtained from the left anterior cingulate cortex (ACC) and thalamus at baseline and 10 months after treatment in 16 patients with psychosis using 4.0 T 1 H magnetic resonance spectroscopy. A neuropsychological test battery was administered at baseline and 1 year. In the ACC, baseline glutamine was associated with performance on the Paced Auditory Serial Addition Task (PASAT). Glutamate at 10 months was associated with Wisconsin Card Sorting Test (WCST) errors and Trail-Making Test-B duration. Glutamine at 10 months was positively associated with WCST errors and negatively associated with WCST categories completed. In the thalamus, baseline glutamine was negatively associated with performance on the PASAT. Thalamic glutamate at baseline showed a trend towards a negative association with social functioning at 5 years. Glutamatergic metabolites were associated with neuropsychological test deficits and impaired social functioning at 5-year follow-up in patients with first episode psychosis, findings suggestive of an association between glutamatergic alterations on neurotoxicity early in the course of schizophrenia. Highlights: Glutamatergic metabolites correlate with cognitive deficits in first-episode psychosis. Thalamic glutamate at diagnosis of psychosis is negatively associated with social functioning at 5-years.